PENYULUHAN DAN PEMERIKSAAN KESEHATAN LANSIA DI DESA SALO TIMUR - Rizki Rahmawati Lestari; Zurrahmi Z.R (COVIT (Community Service of Health), 2021)
Nowadays people are no stranger to hearing the word Hypertension. Hypertension is a disease that is commonly found in the community, and is a disease associated with the cardiovascular system. Hypertension is not a contagious disease, but we also cannot take it lightly, we should always be vigilant. High blood pressure or hypertension and atherosclerosis (hardening of the arteries) are the two main conditions that underlie many forms of cardiovascular disease. Furthermore, it is not uncommon for high blood pressure to also cause kidney problems. Until now, both efforts to prevent and treat hypertension have not been fully successful, this is due to many influencing factors such as lack of knowledge about hypertension (understanding, classification, signs and symptoms, causes and complications) and also its treatment. Currently, the death rate due to hypertension in Indonesia is very high. Hypertension is the number 3 cause of death after stroke and tuberculosis, which reaches 6.7% of the population of deaths at all ages in Indonesia. Hypertension is a circulatory system disorder that causes an increase in blood pressure above normal, which is 140/90 mmHg. The results of the Basic Health Research (Riskesdas) Balitbangkes in 2007 showed the prevalence of hypertension nationally reached 31.7% (Ministry of Health of the Republic of Indonesia). Of that amount, 60% of people with hypertension end up in a stroke. While the rest in the heart, kidney failure, and blindness. While in the Western world, hypertension actually causes kidney failure, because efforts need to be made to reduce the number of hypertension disease, especially for people with hypertension need to be given proper care and treatment so as not to cause complications that are getting worse. In addition, the importance of providing nursing care to hypertensive patients is also very necessary to carry out the correct implementation in hypertensive patients. It is hoped that with this community service about hypertension disorders,it can provide appropriate and correct nursing care for people with hypertension and can reduce morbidity and mortality due to hypertension in the community.